Arab Law Quarterly (jstor)
Economic and commercial developments in Arab countries continue to attract attention. Courts in the non-Islamic world increasingly need to decide issues involving Arab laws and Islamic law generally. This interest in Arab countries, not only internally but externally as well, enhances the need for a topical journal on Arab law.
Keywords: Middle East Studies